Investigation of environmental impacts on explosives by open burning - Galante, Erick (Cranfield University, 2018)
New safety requirements are pressuring military organizations to replace TNT with insensitive high explosives (IHEs) containing DNAN, NTO and RDX but little is known about the behaviour IHE components and formulations in the environment. The environmental impact of ordnance during the in-service phase has been studied, but most reports concern TNT-based legacy explosives and their impact on soil rather than other environmental compartments. To address this knowledge gap, IHE samples ranging from milligrams in a closed system to grams and kilograms in an open system were tested in the laboratory and field, yielding environmental impact data that helps to determine the behaviour of the materials during open burning. The prediction software HYDRUS 1D was then fed with the empirical data and the actual and predicted outcomes for the behaviour of DNAN, NTO, RDX and the IHE formulation were compared to determine whether this software can be used to predict said impacts. The thermodynamic properties of DNAN make it more likely to melt, boil and sublimate during open burning, leaving ~70 % behind as unreacted residues. DNAN also inhibits the burning of RDX and NTO, such the near zero residual mass when these are burned as pure compounds increases to ~20 % of the initial mass when the formulation is burned. Overall, the experiments showed that DNAN-based IHEs behave in a similar manner to TNT-based legacy explosives regarding emission of greenhouse gases, but worse in terms of solid residues. Ultimately, the body of work reported through this thesis has shown that traditional open burning of DNAN-based IHE could leave as much as 12 % (w/w) of unburnt explosive on the soil. We have therefore concluded that the open burning methodology adopted for TNT-legacy munitions should be avoided for disposing of IHE explosives